Letters from Juan de Mata Sevillano, Duque de Sevillano to Ramón María Narváez, Duque de Valencia (1848-1864) - Fernández Escudero, Agustín (Hispania Nova, 2020)
General Narváez, besides his numerous military and political successes, took great care in investing his money diversifying the associated risk and increasing profits, as advised by his banker and fellow party member, the duque de Sevillano. The general’s money was deposited in important financial houses in Paris or London, due to the idea of diversifying and his trips to different European countries. In the frequent correspondence that these two personalities held, from 1848 to 1864, at least from the duque de Sevillano (the Espadón de Loja one addressed to the banker has not been kept), it has been proved that besides writing about financial matters, they also wrote about merely domestic matters; nonetheless, as a correspondent, Sevillano also dedicated many lines of his letters to communicate to his general, when he was absent from Madrid, the details of Spanish politics.